Cuando la petición no tiene sentido: análisis contrastivo de las interrogativas en polaco y español - Nowakowska-Głuszak, Anna (Neophilologica, 2008)
The present article discusses problems that arise while interpretation speech acts such as requests in Spanish and Polish. The analytical perspective of cultural linguistics allows us to demonstrate that some elements of language change their meaning in specific communicative situations, which, as a consequence, may lead to intercultural misunderstanding. This is the case of the questions used as requests. Analyzing possible ways of translating into Polish this kind of phrases in Spanish, we are able to demonstrate that both languages differ in the way they conceptualize such linguistic phenomena as politeness.